2015
DOI: 10.3329/bjvm.v13i1.23712
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Cryptosporidium</i> Infection in Cattle in Maiduguri, North Eastern Nigeria

Abstract: A study was carried out to survey the prevalence of Cryptosporidium infection in cattle in Maiduguri, Northeastern Nigeria. A total of four hundred (400) fecal samples from cattle were randomly collected and examined for the presence of Cryptosporidium sp. oocysts using the modified Ziehl-Neelsen (MZN) staining method. The results showed that the overall prevalence of infection was 22.3%, with an infection rate of23.4% in adult cattle and 19.1% in young cattle, respectively. There was no statistical significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The overall prevalence of Cryptosporidium infection in dairy cattle was 20.5%, which is comparable to other studies from Ghana [ 39 ], Nigeria [ 40 ], and Iraq [ 41 ]. However, the current result is higher than the report of Wegayehu et al [ 27 ], who reported from cattle reared under an extensive management system.…”
Section: Discussionsupporting
confidence: 82%
“…The overall prevalence of Cryptosporidium infection in dairy cattle was 20.5%, which is comparable to other studies from Ghana [ 39 ], Nigeria [ 40 ], and Iraq [ 41 ]. However, the current result is higher than the report of Wegayehu et al [ 27 ], who reported from cattle reared under an extensive management system.…”
Section: Discussionsupporting
confidence: 82%
“…The current study found the overall prevalence of Cryptosporidium infection in dairy cattle was 20.5%. These ndings relatively agree with the results of other studies in cattle, with a prevalence of 23.7% from Ghana (Dankwa et al, 2021), 22.3% from Nigeria (Adamu et al, 2015), and 26.5% from Iraq (Saeed et al, 2019). However, the current result (23.7%) is higher than the report of Wegayehu et al (2013), who reported a 4.7 percent prevalence in dairy cattle reared under an extensive management system.…”
Section: Cryptosporidium Infection In Dairy Cattlesupporting
confidence: 91%
“…Cryptosporidium bovis oocyte can infect six species of livestock and poultry in Tunisia [9]. The prevalence of Cryptosporidium infection in cattle in Northern Nigeria reported to be 22.3% [10,11], whereas the prevalence of Blastocystis spp., Giardia spp., and Entamoeba spp. was 14.6%, 12.45%, and 7.45%, respectively [12].…”
Section: Resultsmentioning
confidence: 99%